Extraction Of Oil From Calophyllum Inophyllum Seeds Optimization And Kinetics Studies Of Ultrasonic-Assisted Extraction - Fuad, Faiznur Mohd (2016)
Calophyllum inophyllum seeds oil was extracted using two different extraction techniques, namely, ultrasonic-assisted extraction (UAE) and Soxhlet extraction (SE). The highest oil yield attained from UAE was 55.44 ± 0.53 % at an extraction time of 20 min, extraction temperature 40 °C, ultrasonic power 210 W, liquid to solid (L/S) ratio 20 mL/g and n-hexane as the solvent. Meanwhile, 70.21 ± 0.36 % of oil yield was obtained from SE when the extraction time was 240 min, extraction temperature 85 °C, L/S ratio 35 mL/g and n-hexane as the solvent. C. inophyllum seeds oil extracted from these two techniques contained similar types of fatty acids such as oleic acid, palmitic acid, linoleic acid, stearic acid and behenic acid. The UAE process of C. inophyllum seeds oil was further optimized using Response Surface Methodology (RSM) via Box-Behnken design (BBD). The maximum predicted oil yield of 56.20 % was obtained at an extraction time of 21 min, extraction temperature 42 °C, ultrasonic power 210 W, L/S ratio 21 mL/g with n-hexane as the solvent. For the kinetics evaluation of UAE process of C. inophyllum seeds oil, it was found that the Patricelli’s model fitted well to the extraction data with R2 > 0.974 and MRPD value < 10 %. Thus, it is adequate to describe the extraction process of oil from C. inophyllum seeds.